Cation diffusion facilitator proteins of Beta vulgaris reveal diversity of metal handling in dicotyledons. (5th February 2023) - Alejandro, Santiago; Meier, Bastian; Hoang, Minh Thi Thanh; Peiter, Edgar
Abstract: Manganese (Mn), iron (Fe), and zinc (Zn) are essential for diverse processes in plants, but their availability is often limiting or excessive. Cation diffusion facilitator (CDF) proteins have been implicated in the allocation of those metals in plants, whereby most of our mechanistic understanding has been obtained in Arabidopsis. It is unclear to what extent this can be generalized to other dicots. We characterized all CDFs/metal tolerance proteins of sugar beet ( Beta vulgaris spp. vulgaris ), which is phylogenetically distant from Arabidopsis. Analysis of subcellular localization, substrate selectivities, and transcriptional regulation upon exposure to metal deficiencies and toxicities revealed unexpected deviations from their Arabidopsis counterparts. Localization and selectivity of some members were modulated by alternative splicing. Notably, unlike in Arabidopsis, Mn‐ and Zn‐sequestrating members were not induced in Fe‐deficient roots, pointing to differences in the Fe acquisition machinery. This was supported by low Zn and Mn accumulation under Fe deficiency and a strikingly increased Fe accumulation under Mn and Zn excess, coinciding with an induction of BvIRT1 . High Zn load caused a massive upregulation of Zn‐BvMTPs . The results suggest that the employment of the CDF toolbox is highly diverse amongst dicots, which questions the general applicability of metal homeostasis models derived from Arabidopsis. Summary statement: Cation diffusion facilitators, called metal tolerance proteins (MTPs) in plants, mediate the transport of metals out of the cytosol. Roles of these transporters in metal homeostasis have been inferred mainly from work on model species. It is unclear to what extent these findings can be generalized. Here we show that sugar beet MTPs often deviate from their Arabidopsis counterparts in terms of substrate spectrum, subcellular localization, as well as transcriptional regulation upon exposure to Fe, Mn, and Zn deficiency and Mn and Zn toxicity. The results indicate a diverse employment of these proteins in phylogenetically distant dicots.